DESIGN AND IMPLEMENTATION OF LMS-BASED HYBRID LEARNING MODEL FOR CIVICS AT SMP NURUL MUKMININ JEMBER - Ayu Qinaroh Khoridatun Nafisah Putri; Hariyanto Hariyanto; I Wayan Wesa Atmaja (STKIP Persada Khatulistiwa Sintang, 2025)
This study aimed to Design and Implement a contextual LMS-based hybrid learning model for Civic Education (PPKn) among eighth-grade students at SMPI Nurul Mukminin Jember. The study was motivated by the low effectiveness of learning due to the lack of an appropriate hybrid learning Design and underutilized LMS platforms. Using a qualitative approach with a case study method, data were collected through observation, interviews, and documentation. The findings revealed that a hybrid learning model combining flipped classroom and station rotation strategies with contextual learning effectively enhanced students’ learning outcomes and instructional effectiveness. The LMS played a significant role in delivering digital content, facilitating online discussions, and supporting formative assessments. The study concludes that a contextually Designed LMS-based hybrid learning model increases student engagement and learning achievement, offering an alternative solution for 21st-century education.